Identifying cost drivers of next generation networks with respect to telecom services and possible cost saving areas - Gunaratna, Hettiarachchige Wikum Dhammika; Winai Wongsurawat; Donyaprueth Krairit; Sundar Venkatesh; Government of Korea (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
The telecommunication industry is challenged by a significant increase in the complexity of information transfer due to a recent information technology. As the result, telecommunication industry is facing a fundamental paradigm shift, with the convergence of voice and data services as well as ever expanding technologies to its users. This technological movement towards a convergence of telephony and computer technologies, internet protocol based networks, and wired and wireless services is creating areas of tremendous opportunities. These networks often called next generation networks. Regulation of NGN is becoming complex than ever. Interconnection is the main key challenging area and legacy practices may be difficult to apply as it is. However, application of LRIC-bottom up approached is ac cepted as the best suited considering many circumstances. Application of LRIC- bottom- up approach helps understand cost drivers of NGN since it is wide discussion it may cha nge. Capability of providing many services through one network lead to possible cost savings
Submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in International Business
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2008
A research study submitted in submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, AIT, Thailand
Submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in International Business
Keywords: Telecommunication -- Costs